Penegakan Hukum Pidana Dalam Kasus Pemalsuan Dokumen Oleh Mafia Tanah (Studi Putusan No. 65/PID.B/2024/PN.PTI): Criminal Law Enforcement in Cases of Document Forgery by Land Mafia (Study of Decision No. 65/Pid.B/2024/PN.PTI) - Lidya Christina Wardhani; Suyoto; Evelin Aulia (Fundamental: Jurnal Ilmiah Hukum, 2026)
Criminal law enforcement plays an essential role in ensuring legal certainty and protecting public rights in the field of land administration. However, technological development and the modernization of land administration have also created opportunities for the emergence of land mafia practices, particularly through document forgery. This study aims to analyze the concept of criminal law enforcement within the national legal system and its application to land mafia practices through an examination of Decision Number 65/Pid.B/2024/PN.Pti. The research employs a normative legal method using a case approach and a statutory approach. The results indicate that the defendant’s actions in the case fulfill the elements of document forgery as regulated in the Indonesian Criminal Code. The panel of judges adopted a substantive approach by considering not only the formal aspects of forgery but also the legal and social consequences, namely losses suffered by other parties and the disruption of legal certainty over land rights. This study concludes that criminal law enforcement against land mafia practices must be carried out firmly and comprehensively, not only by punishing individual offenders but also by dismantling criminal networks and strengthening the land administration system to prevent similar practices in the future.